STUDYING THE LEVEL OF COMPLEXITY OF TRANSLATION OF POETIC TEXTS - Shakirova, Saida (Журнал иностранных языков и лингвистики, 2023)
The relevance of the translation of poetic texts is increasing every year. Times change, poets change and their writing styles change, but the main problems for translators remain. The authors of the translation should take into account the stylistic, lexical, grammatical, syntactic, semantic, and morphological features present in any poetic work written in any foreign language. In addition, the translator needs to add personal qualities and skills to this type of translation. The clearer and more adequate the translation, the more accurate and real the original is conveyed with all images, plot details, place, and time.